Factors Affecting Job Satisfaction of Nurses Esfahan City Hospitals in Iran - Baboukani, Mehdi Karimi (2010)
The purpose of this study is to find factors that affect the job satisfaction of nurses in Esfahan City hospitals. This study will help hospital administrators to reduce turnover rates and increase recruiting and retention rates. This study indicates that there is a significant relationship between work itself, hospital atmosphere and workload with nurses\' job satisfaction. The result of this study will help nurse managers to implement strategies that meet the unique needs their staffs and organizations.